Implementasi Bauran Pemasaran Dalam Meningkatkan Penjualan Menurut Ekonomi Islam - Zahrah Zahrah; Mellya Embun Baining; Dessy Anggraini (STEKOM PRESS, 2024)
Marketing mix ​​used achieve marketing goals. Using a qualitative research method, a descriptive approach. The findings show that the implementation of the marketing mix increases the sales volume at the Kita Family Building Store, namely in terms of products it still focuses on building equipment such as cement, sand, bricks, etc. Marketing it using media is very simple and according to the Islamic Economics Perspective, the implementation of the marketing mix for the Our Family Building Store seems to be in accordance with Islamic marketing. To a large extent, the concept of Islamic marketing is in accordance, namely in terms of products, always being honest and prioritizing product quality. In terms of price, set the price according to the quality of the product. then in terms of promotion, always emphasize ethics in business, don't cheat, don't sell products that are forbidden by religion, never force consumers to buy their product.